USARP Method: Eliciting and Describing USAbility Requirements with Personas and User Stories - Oliveira, Gabriel F. de; Ferreira, Bruna; Marques, Anna Beatriz (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2020: Anais do XXXIV Simpósio Brasileiro de Engenharia de Software, 2020)
Usability is considered one of the main attributes of software quality. Thus, it becomes necessary to deal with usability requirements at early stages of software development. The cost of solving usability problems at these stages is lower, as it requires less time and effort from the development team. However, there is still a need for solutions that can support the inclusion of usability at early stages of development. In this context, this paper presents USARP, a method to elicit and describe USAbility Requirements with Personas and user stories. The proposed method was created by adopting Design Science Research. USARP proposes the joint use of: (i) a technique for creating personas, (ii) user stories for specifying requirements and (iii) guidelines for eliciting functional usability aspects for enriching the user stories. A feasibility study with novice software engineers was performed to validate the effectiveness and the suitability of the procedures proposed in the method. The results showed that the method is effective in obtaining the usability requirements. In addition, some improvements in its use procedures were identified. A new version of the method was developed based on the results.